Asuhan Kebidanan Komprehensif pada Ny. M di RSIA Masyita Makassar - Nimatul Aliyah; Azrida Machmud; Halida Thamrin (Window of Midwifery Journal, 2026)
Continuous midwifery care is a service provided from pregnancy, childbirth, the newborn period, postpartum, to family planning. The purpose of this study was to describe the implementation of comprehensive midwifery care for Mrs. M at RSIA Masyita Makassar. This study used a case study method with the 7-step Varney management approach and SOAP documentation, including anamnesis, physical examination, supporting examinations, and developmental observation. The results showed that Ny. M experienced a normal pregnancy with six ANC visits, spontaneous labor without complications, and a full-term newborn (birth weight 3,150 grams; length 47 cm). Newborn care was provided according to standards, and the postpartum period progressed well with gradual perineal wound healing. The mother chose a 3-month injectable contraceptive following counseling. It is concluded that the comprehensive midwifery care provided to Ny. M was in accordance with existing theories, with no gaps identified between practice and service standards.